Comparison of transabdominal sonography and transvaginal sonography in evaluation of endometrial thickness in the setting of abnormal uterine bleeding - R, Sam Raja; Ramakrishnan, Karthik Krishna; Sekar, Aadithiyan; Subbiah, Meenakshi; Natarajan, Paarthipan (Eastern Journal of Medical Sciences, 2023)
Background: Abnormal uterine bleeding (AUB) is a common complaint in women of reproductive age for which they consult their gynecologist and is the direct cause of a significant health-care burden for women. Imaging plays a pivotal role in diagnosing and helping the clinicians choose an appropriate management strategy at the earliest possible juncture, thus relieving patients of their symptoms and preventing complications. This tertiary care hospital-based study aims to assess the role transabdominal sonography in comparison with transvaginal sonography in evaluation of endometrial thickness in the setting of AUB in of in female population of Kancheepuram and West Chennai district of Tamil Nadu. Materials and Methods: It is a prospective study conducted in the Department of Radiology, of a tertiary care hospital in Kancheepuram district of Tamil Nadu, India. One hundred adult females who presented with complaints of abnormal bleeding per vaginum underwent both transabdominal (TAS) and transvaginal ultrasonography (TVS). In addition, they were evaluated for AUB through assessment of endometrial thickness and the presence of other uterine and adnexal pelvic pathologies. Result: The results of the present study show that TVS is superior to TAS in assessing endometrial thickness accurately and has a slightly better role in diagnosing endometrial pathologies such as endometrial polyp, hyperplasia, endometrial carcinoma, and number and location of Submucosal/intramural leiomyomas. Conclusion: TVS is superior to TAS in assessing endometrial thickness accurately and have high sensitivity and accuracy in the diagnosis of pelvic pathologies and determination of the type of pelvic mass was improved significantly when a transvaginal study was performed after TAS in cases of AUB.